Brilliant Green Dye Biosorption Using Activated Carbon Derived from Guava Tree Wood - R. A. Mansour; Abeer El Shahawy; A. Attia; Mokhtar S. Beheary (International Journal of Chemical Engineering)
The removal of brilliant green (BG) dye from an aqueous solution using activated carbon (AC) derived from guava tree wood is conducted in batch conditions. The influence of different factors such as contact time, pH, adsorbent dosage, initial dye concentration, and temperature on the adsorption of BG onto AC was investigated. FTIR, BET, and SEM analyses were performed to determine the characteristics of the material. The isotherm results were analyzed using the Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherms. Linear regression was used to fit the experimental data. It was found that the equilibrium data are best represented by the Freundlich isotherm, and the adsorption capacity (qe) was 90 mg dye/g AC. The values of the free energy (∆G), enthalpy (∆H), and entropy (∆S) were −86.188 kJ/mol, 43.025 kJ/mol, and 128 J/mol.K, respectively, at pH 7 for the BG dye. The kinetics of BG dye adsorption were analyzed using pseudo-first-order and pseudo-second-order models, and it was found that the pseudo-second-order model was suitable for the behavior of the BG dye at R2 = 0.999.